PENERAPAN METODE MEMBACA NYARING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR: SYSTEMATIC LITERATURE STUDY - Maudy Aprilia; Geby Chrilda Putri Abdi; Ardya Syaqibilla Nadine; Siti Aminah; Andi Gusmaulia Eka Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the application of the read aloud method in Indonesian language learning and analyze the extent to which this method can improve early reading skills in first-grade elementary school students. This research employs a Systematic Literature Study (SLS) approach guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. A total of 120 articles were identified from Google Scholar, published between 2020 and 2026. After deduplication and systematic screening based on inclusion and exclusion criteria, 15 articles were selected for final analysis. Findings consistently demonstrate that the read aloud method effectively develops phonemic awareness, letter recognition, and reading fluency among first-grade students. The level of developmental achievement increased from 32.74 at pre-intervention to 50 at the end of the second cycle. Two critical success factors were identified: the quality of teacher-student interaction and the selection of developmentally appropriate texts. Teachers who employed expressive intonation, varied facial expressions, and open-ended questions significantly enhanced student comprehension and engagement. Texts featuring high sound repetition and rhyme patterns facilitated letter-sound correspondence mapping more effectively. The holistic approach of read aloud proved more inclusive for students with limited pre-school literacy exposure, as it allows meaning-first entry into reading rather than requiring sequential letter mastery. This study contributes to early literacy theory by identifying the auditory-visual dual processing mechanism as the cognitive basis for the method's effectiveness, and offers practical implications for literacy program development in Indonesian elementary schools.